Exclusive production of D+sD−s, D*+sD−s, and D*+sD*−s via e+e− annihilation with initial-state radiation - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We perform a study of exclusive production of D+sD−s, D*+sD−s, and D*+sD*−s final states in initial-state-radiation events from e+e− annihilations at a center-of-mass energy near 10.58 GeV, to search for charmonium 1−− states. The data sample corresponds to an integrated luminosity of 525 fb−1 and was recorded by the BABAR experiment at the PEP-II storage ring. The D+sD−s, D*+sD−s, and D*+sD*−s mass spectra show evidence of the known ψ resonances. Limits are extracted for the branching ratios of the decays X(4260)→D(*)+sD(*)−s.
Gesehen am 23.08.2023
Im Titel sind das Plus- und Minuszeichen und das Sternchenzeichen hochgestellt, der Buchstabe "s" tiefgestellt